Design, analysis, and fabrication of solar power bank using recycle battery / Aqil Hafiz Tsen Loong Tyan - Tsen Loong Tyan, Aqil Hafiz (2022)
Power bank is very helpful and it is commonly used in worldwide to keep smartphone always on. It is also portable to brought it wherever we go. However, it is not very suitable for some activities and situation. This can be proven when we bring the power bank along with us for a camp or climb for a few days or longer, because the battery capacity of the power cannot last long. Thus, to overcome this problem we re-design the power bank by adding a solar panel that can fit and portable enough for us use it. The purpose of the solar panel is to make the battery rechargeable using the sun light instead using a wire and maybe we will make it waterproof so that it can stand tough for an outdoor activities. In the other hand, it also suitable for normal usage such as hang out with friends and many others. Furthermore, the design of this power bank is more friendly user than the normal power bank